A Practical Catalyst-Free Synthesis of 6-Amino-4 Alkyl/Aryl-3-methyl-2,4-dihydropyrano[2,3-c]pyrazole-carbonitrile in Aqueous Medium - Manisha Bihani; Pranjal P. Bora; Ghanashyam Bez (Journal of Chemistry)
A completely green and improved method for the synthesis of 6-amino-4-aryl-3-methyl-2,4-dihydropyrano[2,3-c]pyrazole-carbonitriles by a four-component reaction of a mixture of ethyl acetoacetate, hydrazine hydrate, aldehyde, and malononitrile in boiling water is reported. Similar synthesis starting from aliphatic aldehydes was carried out in water: ethanol (1 : 1) at reflux temperature without using any catalyst.